Sustainable Food Security in New Kalimantan in the Context of IKN Development - Silalahi, Verry Albert Jekson Mardame; Silalahi, Violetta Hosiana Christella (PT FORMOSA CENDEKIA GLOBAL, 2024)
Food security is a crucial issue for Indonesia, especially in the face of increasing population and urbanization. This research examines sustainable food security in East Kalimantan in the context of the development of the nation's capital. The purpose of this research is to identify agricultural strategies and innovations, logistics solutions, economic policies, and nutrition education programs that can improve food security in East Kalimantan. The research method used is a literature study with content analysis of various related literature. The results show that the application of modern agricultural technology, digital platforms for food distribution, social assistance programs, and nutrition education can significantly improve food security. The development of IKN also provides an opportunity to integrate food security policies with sustainable development strategies. The conclusion of this study emphasizes the importance of collaboration between the government, private sector and communities to implement these strategies to achieve sustainable food security in East Kalimantan.